2011
DOI: 10.2134/jeq2009.0515
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Ammonia, Methane, Carbon Dioxide, and Nitrous Oxide from Dairy Cattle Housing and Manure Management Systems

Abstract: Concentrated animal feeding operations emit trace gases such as ammonia (NH 3 ), methane (CH 4 ), carbon dioxide (CO 2 ), and nitrous oxide (N 2 O). The implementation of air quality regulations in livestock-producing states increases the need for accurate on-farm determination of emission rates. The objective of this study was to determine the emission rates of , respectively. The open lot areas generated the greatest emissions of NH 3 , CO 2 , and N 2 O, contributing 78, 80, and 57%, respectively, to total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
145
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 34 publications
(65 reference statements)
19
145
7
1
Order By: Relevance
“…It has been demonstrated on dairies in southern Idaho that emissions of both NH 3 and CO 2 occur from lagoons and typically increase from spring to fall following increases in temperature (Bjorneberg et al, 2009, Leytem et al, 2011, 2013. As the amount of CO 2 generated from lagoons is much greater than the amount of NH 3 (Leytem et al, 2011), the pH of the lagoon water would likely increase as these emissions increased, which was demonstrated in the lagoons in the present study. The specific conductivity tended to increase over time, with D5 and D6 showing the strongest trends ( fig.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonssupporting
confidence: 57%
See 1 more Smart Citation
“…It has been demonstrated on dairies in southern Idaho that emissions of both NH 3 and CO 2 occur from lagoons and typically increase from spring to fall following increases in temperature (Bjorneberg et al, 2009, Leytem et al, 2011, 2013. As the amount of CO 2 generated from lagoons is much greater than the amount of NH 3 (Leytem et al, 2011), the pH of the lagoon water would likely increase as these emissions increased, which was demonstrated in the lagoons in the present study. The specific conductivity tended to increase over time, with D5 and D6 showing the strongest trends ( fig.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonssupporting
confidence: 57%
“…The formation of NH 3 in solution generates H + and reduces the pH, and the formation of CO 2 (utilization of H + ) in solution increases pH (Ni, 1999;Chaoui et al, 2009). It has been demonstrated on dairies in southern Idaho that emissions of both NH 3 and CO 2 occur from lagoons and typically increase from spring to fall following increases in temperature (Bjorneberg et al, 2009, Leytem et al, 2011, 2013. As the amount of CO 2 generated from lagoons is much greater than the amount of NH 3 (Leytem et al, 2011), the pH of the lagoon water would likely increase as these emissions increased, which was demonstrated in the lagoons in the present study.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonsmentioning
confidence: 99%
“…For groups of cattle at the field or paddock scale (< 0.5 km 2 ), tracer release (Griffith et al, 2008;Leytem et al, 2011), the integrated horizontal flux method (Laubach and Kelliher, 2004;Griffith et al, 2008), and the point-source dispersion modelling and measurement approach (McGinn et al, 2011;McGinn and Beauchemin, 2012) have demonstrated their usefulness. At the farm scale in-between (≈ 0.5-5 km 2 ), McGinn et al (2006) have used a combination of tracer release, line-averaged concentration measurements, and inverse modelling of fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization and quantification of N2O and CH4 emitted from livestock operations are important because these gases are believed to play a major role in the increase of Earth's temperature. During the last two hundred and fifty years, anthropogenic activities, including demanding agricultural production, have increased the global atmospheric concentration of GHG, namely CO2, CH4, and N2O by 36,148, and 18%, respectively [1]. Total greenhouse gas (GHG) emissions in the US increased by 14.7% from 1990 to 2006.…”
Section: Introductionmentioning
confidence: 99%